The Effect of Supplementation of Oregano Oil and Probiotic on Intestinal Microbes (Namely E. coli spp., Salmonella spp., Clostridia spp.) of the Broiler Chicken - Rewatkar, Harshal N.; Wankhede, S. M.; Agashe, J. L.; Padole, R. M.; Jadhao , A. D.; Jadhao, G. M. (International Journal of Livestock Research, 2019)
To evaluate the effect of oregano oil and probiotic on total microbial count of intestine namely E. coli, Salmonella and Clostridia. On 42nd day, 8 birds from each treatment were slaughtered by decapitation. The digestive tracts were dissected and described Caecal content samples were taken aseptically and were transferred into sterile plastic bags and immediately transported in cold chain to the laboratory, samples diluted, cultured and checked for the presence of organisms in samples (E. coli, Salmonella, Clostridia) and compared with the control after incubation. Results were expressed as log10 colony-forming units per gram of ileal digesta (log10 CFU/gram). The intestinal microbial count namely E. coli, Salmonella, Clostridia were significantly decreased in T3 than in groups T2, T1 and control. It was concluded that feeding of Oregano essential oil and probiotic- Saccharomyces cerevisiae exhibited beneficial effect on GIT and decreased the harmful microbial count of the intestine in the broiler chicken.